Rear-fanged snake venoms: an untapped source of novel compounds and potential drug leads - Saviola, Anthony J. (2014)
Animal venoms represent a diverse source of potentially valuable therapeutic compounds due to the high specificity and the potent biological activity of many toxins. Snake venom toxins, particularly disintegrins and proteases from viper venoms, have yielded therapeutics with anti-cancer and hemostatic dysfunction activities. However, venoms from rear-fanged ??colubrid?? snakes have rarely been analyzed from the perspective of potential lead compound development. Here, we discuss recent progress in the analysis of these venoms, focusing on several studies of specific venom components as well as transcriptomic and proteomic surveys. Currently available ?omic technologies largely circumvent the problematic low venom yields of most rear-fanged snakes, and because their basic biology is often very different from the well-studied front-fanged snakes, there is great potential for novel compound discovery in their venoms.